You are on page 1of 12

# Limiting State Probabilities

## Matrix Multiplication Method:

1
Up

2
Down
1

t .
t
stochastic transitional probability matrix, P = 1 1 - .
2 .
t 1 - .
t

1
For limiting state probabilities evaluation, P = 1 1 -
t terms disappear during computation
2
limiting state probability vector, = [P1 P2]
Using the equation P = ,
[P1 P2]

1-
= [P1 P2]

1-

## The two matrix equations are:

) = P1
P1.(1 - ) + P2.(

or - P1 + P2 = 0

P1.(
) + P2.(1 - ) = P2

or

P1 - P2 = 0

1-

If t was used in the P matrix, then the two equations would be:
- t P1 + t P2 = 0
t P1 - t P2 = 0
since t is finite & non-zero, it is cancelled out resulting:
- P1 + P2 = 0
P1 - P2 = 0

## The same equations as the case where

t was not used in the P matrix

## These are identical equations that can be written as:

P2

.. Eq. 1

P1 + P2 = 1

.. Eq. 2

P1 =
The other equation is

P1 = A =

P2 = U =

2

1
Both
Up

2
1 Up
1 Down

3
Both
Down

## State Space Diagram

1

stochastic transitional
probability matrix,

1 1-2
2

0
P = 2 1-
-

3 0
2
1-2

2 .
t 1 - .
t

## limiting state probability vector, = [P1 P2 P3]

Using the equation P = ,
[P1

1-2
2

0
P2 P3] 1-
-

0
2
1-2

2 .
t 1 - .
t

P1.(1 - 2
) + P2.(
) = P1
P2.
+ P3.(1 - 2
) = P3

= [P1 P2 P3]

or - 2
P1 + P2 = 0 Eq. 1
or P2 - 2
P3 = 0 Eq. 2
P1 + P2 + P3 = 1 Eq. 3

2
P1 =
,
( + )2

2
P2 =
( + )2

and

2
P3 =
( + )2

## Limiting State Probabilities

Alternate Method:
2

1
Both
Up

2
1 Up
1 Down

Both
Down

## State Space Diagram

Availability of each component,

A=

U=

P1 = P(Both Up)

=A

## P2 = P(1 Up, 1 Down) = 2AU

P3 = P(Both Down)

=U

2
=
( + )2

2
( + )2

2
=
( + )2

1
Failure rate, =
m

Repair rate, =

1
Up

1
r

Pup =

2
Down

m
m
1/
f
=
=
=
=
+
m+r
T
1/f

## where, T = mean time between failures

f = freq of encountering the Up state = Pup .
Similarly,

## Frequency of encountering State i

= P(being in State i) x (rate of departure from State i)
= P(not being in State i) x (rate of entry from State i)
This concept can be used to deduce limiting state probabilities
when the transition rates are known
Frequency Balance Approach

1
Up

2
Down

## Frequency of encountering State 1

= P(being in State 1) x (rate of departure from State 1)
= P(not being in State 1) x (rate of entry from State 1)
= P1.
= P2.
.. Eq. 1
Similarly, Frequency of encountering State 2
= P1.
.. Eq. 2
= P2.
Eq. 1 and 2 are the same equations. The other equation is
P1 + P2 = 1 .. Eq. 3
Solving Equations 1 and 3,

## mean duration in State i, mi =

m1 = MTTF =

P1 =

and P2 =
+
+

1
rate of departure from State i

m2 = MTTR =

2

1
Both
Up

1 Up
1 Down

3
Both
Down

## State Space Diagram

Using Frequency Balance Approach:
Frequency of encountering State 1,
= P2.

P1.2

Eq. 1

## Frequency of encountering State 2,

) = P1.2
+ P3.2
Eq. 2
P2.( +
Frequency of encountering State 3,
= P2.

P3.2

Eq. 3

## Only two of the above 3 equations are independent.

The other equation is,

P1 + P2 + P3 = 1

## Solving Equations 1, 3 and 4,

2
2
2
P1 =
, P2 =
and P3 =
( + )2
( + )2
( + )2

... Eq. 4

Reliability/Availability Evaluation
in Repairable Systems
2

1
Both
Up

2
1 Up
1 Down

3
Both
Down

## Availability: probability of finding the system in the up state

A = P1 + P2 = 1 U

2
Unavailability, U = P3 =
( + )2
Reliability:
- probability of staying out of the failed state
- failure states absorbing states
- time dependent probability
- limiting state reliability = 0
- MTTF (average time before the system enters the
absorbing state) can also be calculated
o differential equations method
o truncated matrix method

1
Both
Up

2
1 Up
1 Down

3
Both
Down

## The differential equations are:

P1(t) = - 2
P1(t)

--- Eq. 1

P2(t) =

2
P1(t) P2(t) --- Eq. 2

P3(t) =

P2(t)

--- Eq. 3

## Solving the equations using Laplace Transform, we get

P1(t), P2(t) and P3(t)
Rs(t) = P1(t) + P2(t)
For non-repairable components, we can directly apply Product
Rule of Unreliability for a parallel system:
Qs(t) = Q1(t) x Q2(t) = (1 - e t ) (1 - e t )
Rs(t) = 1- Qs(t) = 2 e t - e 2 t

3
MTTF = R s ( t )dt =
2
0

2

1
Both
Up

2
1 Up
1 Down

3
Both
Down

P1(t) = - 2
P1(t) + P2(t)

--- Eq. 1

P2(t) =

2
P1(t) (
+ ) P2(t)

--- Eq. 2

P3(t) =

P2(t)

--- Eq. 3

## Solving the equations using Laplace Transform, we get

P1(t), P2(t) and P3(t)
Rs(t) = P1(t) + P2(t)

MTTF =

R s ( t )dt =
0

3 +
2 2

## MTTF using Truncated Matrix Method

In discrete Markov chain:
average # of time intervals before entering the absorbing state is
given by
N = [ I Q ] -1
where,
I = identity matrix
Q = truncated matrix created by deleting row(s) and column(s)
associated with the absorbing states

## In continuous Markov process:

Average time before the system enters the absorbing state (i.e.
MTTF) is given by
M = [ I Q ] -1
where,
M = termed as the fundamental matrix
mij = average time spent in State j before being absorbed,
given that the process starts in State i

1
Both
Up

2
1 Up
1 Down

Both
Down

stochastic transitional
probability matrix,

1 1-2
2

P = 2 1-
3 0
0
2 .
t 1 - .
t
1

1
2

1 1-2
2

Q = 2 1-
-

M = [ I Q ] 1

={

1
0

0
1

1-2
2

1-
-

} -1 =

1 +

2 2

3 +
2
2

## If the system starts in State 2, MTTF = m21 + m22 =

2 +
2
2

If Series System:
States 2 and 3 are the absorbing states, Q = [ 1-2
]
M=[IQ]

= [ 1 1 + 2
]

1
= 2